VEDIC ASTRONOMY AND ASTROLOGY AND ITS PRACTICAL APPLICATION IN MODERN ERA: A CASE STUDY - Sashibhusan Mishra (Veda Jyotih: Jurnal Agama dan Sains, 2024)
India also has a very long history of traditional science through the ages through its various epoch-making traditional scriptures. Major traditional scientific texts and scientific elements are composed directly or indirectly in the Sanskrit Language and are mostly related to ancient Indian Vedic literature. Among several branches of traditional Indian sciences, the most ancient branches are, in most cases, astronomy, medicine, etc. India also has a very long history of astronomical sciences (jyotiḥ-sāstra) and medicine (āyur-veda). Indian classical astronomical sciences are roughly divided into mathematical astronomy (gaṇita-jyotiṣa) and astrology (phalita-jyotiṣa). All these scriptures directly or indirectly influenced Indian culture and life. Even today Indian people are following the directions of these sacred texts. Here I would like to do a case study of the only hospital related to Indian Astrology and Astronomy. The name of the hospital is ‘Unique Sangeeta Memorial Hospital’ and it is dedicated to the service of mankind with a mixture of traditional Vedic Astrology and Astronomy and modern Medical knowledge.